The profile of acute glomerulonephritis among Indonesian children - Husein Albar; Syarifuddin Rauf (Indonesian Pediatric Society Publishing House, 2016)
Background Acute glomerulonephritis (AGN) is a form of glom- erulonephritis characterized by sudden and explosive onset of glom- erular injury symptom. It usually occurs after recent infection by group A beta-hemolytic streptococcus. AGN among Indonesian children seems to be less frequently reported than that among other countries. Objective To determine the current profile of AGN among Indo- nesian children hospitalized in eleven teaching centers. Methods This was a descriptive, cross-sectional study, based on a review of the standard medical records of 509 children with AGN hospitalized in 11 teaching centers in Indonesia over a five-year period (1997-2002). Data extracted from the medical records con- sisted of history of illness, clinical and laboratory findings, and chest X-rays. Results Age of the patients at the onset of AGN ranged from 2.5 to 15 years, with peak age of 8.5 years. The majority (76.4%) was above 6 years old with male predominance (58.3%). About 68.9% and 82% of the patients came from low socioeconomic and low edu- cational status families. Antecedent upper respiratory infections were observed in 45.8% cases and pyoderma in 31.6%. The disease seemed to be more commonly elicited by streptococcal infection than by other infections, as proved by an elevated anti-streptolisin O (ASO) titer (66.6%) and decreased C 3 concentrations (60.4%). The frequent clinical features included periorbital edema (76.3%), hypertension (61.8%), and gross hematuria (53.6%). The most preva- lent laboratory findings were microhematuria (99.3%), proteinuria (98.5%), raised erythrocyte sedimentation rate (85.3%). The initial chest X-rays showed pleural effusion (81.6%) and cardiomegaly (80.2%), whereas echocardiogram documented pericardial effusion (81.6%). Acute pulmonary edema (11.5%), hypertensive encepha- lopathy (9.2%), and acute renal failure (10.5%) were frequent com- plications noted in our study. Conclusion Despite no adequate data on throat or skin cul- tures, AGN among Indonesian children seems mostly to be poststreptococcal AGN as proved by the elevated ASO titer and decrease in serum C 3 concentration